Reading Interest Upon Scientific Articles - Annisaa - Nahdatul Sholehah; Tri - Kurniawati; Finny - Anita (Journal of English Language Teaching and Education (JELTE), 2023)
This study aims to determine the level of interest in reading scientific articles by prospective English teachers and the factors that influence reading interest in scientific articles to prospective English teachers. The subjects of this study were 86 students in the fifth semester of the English Education study program. The form of this research is descriptive with a mixed method approach where data about interest in reading scientific articles is collected using questionnaires and interviews. data analysis using descriptive statistics and descriptive narrative. Then, the results of student responses to the questionnaire were analyzed through descriptive percentage levels, reading interest upon scientific articles, with the percentage of student responses that answered high. The analysis of interviews conducted by the researcher unveiled multiple factors that affect students' enthusiasm for reading scientific articles. These factors can be categorized into two main groups: a) internal factors, which encompass emotions, attentiveness, and motivation, and b) external factors, including the lecturer's role, the learning environment, and available resources.